Enantioselective immobilized lipase - Basri, Mahiran; Othman, Siti Salhah; Jasmani, Halila; Hussein, Mohd Zobir; Abdul Rahman, Mohd Basyaruddin; Raja Abdul Rahman, Raja Noor Zaliha (2008)
Immobilization of Candida rugosa lipase on a carrier selected from the group consisting of macroporous adsorbent resin of the acrylic type, synthetic epoxy activated resin and Mg--Al-hydrotalcite enhances its enantioselectivity by six to seven folds. The immobilized Candida rugosa lipase is suitable for use in resolution of racemic alcohols and/or carboxylic acids, particularly in resolution of racemic menthol or production of menthyl esters.